Adaptogenic Potential of a Polyherbal Natural Health Product: Report on a Longitudinal Clinical Trial. Issue 3 (2007) - Seely, Dugald; Singh, Rana
Abstract : Stress is a risk factor for a number of diseases and is an important predictor of health in general. Herbal medicines have been used as adaptogens to regulate and improve the stress response and there is evidence to support the use of herbal medicines for this purpose. We conducted an open-label longitudinal study on the natural health product, OCTA©, a compound mixture of eight herbs, to determine its effects on perceptions of stress. Eighteen participants were enrolled in the study and were followed over a period of 3 months. Primary endpoints included scores from four validated questionnaires (SF-36v2, PSS, STAI and BDI-II), serum DHEA, ALT, AST and creatinine all measured at 12 weeks. Seventeen patients completed the study. Except for the physical summary score of the SF36 questionnaire, all the subjective scores indicated a highly significant ( P < 0.0001) improvement in the participants' ability to cope with stress. No adverse effects were reported and there was no evidence of damage to the liver or kidney based on serum markers. Initial evidence for this polyherbal compound supports its potential as an effective 'adaptogenic' aid in dealing with stress. Further research using a randomized controlled design is necessary to confirm the findings from this pilot study.